Managing water resources from the energy - water nexus perspective under a changing climate: A case study of Jiangsu province, China. (March 2019) - Zhou, Yuanchun; Ma, Mengdie; Gao, Peiqi; Xu, Qiming; Bi, Jun; Naren, Tuya
Abstract: As one of the most developed provinces in China, Jiangsu province is facing both energy and water stresses. The impact of energy production on water resource remains to be seen, especially in terms of a changing climate. In this study, we adopt a Long-range Energy Alternatives Planning System (LEAP) model combined with plant-level data to study the impact of energy policies on water resources management. The results indicate that energy efficiency improvements and industry structure optimization can result in 40% and 33% water withdrawal savings respectively in the future depending on the level of optimization. With several integrated measures, total water use can meet the 2030 targets set by the Jiangsu provincial government. Shifts in cooling technology can bring significant water-savings benefits and help fulfill water use-control targets. Furthermore, we find that the Suzhou and Xuzhou administrative areas will experience power output efficiency reductions and will need more water in 2030 under the RCP45 and RCP85 scenarios. More efforts are needed to mitigate climate change and offset its negative impact on energy and water resource. The results of this study will be informative for both resource management and policy design. Highlights: Impacts of energy management actions of Jiangsu Province are studied. Detailed energy production water demand map is drawn for prefecture-level cities. Plant-level bottom-up approach is combined with high-resolution climate scenarios. Climate change may offset water saving effect of other actions.